2003
DOI: 10.1002/jez.a.10278
|View full text |Cite
|
Sign up to set email alerts
|

Oogenesis and plasma levels of sex steroids in cultured females of brown trout (Salmo trutta linnaeus, 1758) in Chile

Abstract: Naturalized brown trout populations in Chile are a valuable genetic resource with aquaculture potential. The oogenesis of a three-year-old brown trout cultured population was studied in southern Chile. Gonadosomatic index (GSI), oocyte growth, gonadal microscopic characteristics, and plasma levels of estradiol-17beta (E2), testosterone (T), and 17alpha-hydroxyprogesterone (17alpha-HP) were measured bimonthly for a nine-month period before spawning. The maximum GSI level (22%) was similar to that described for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
8
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 21 publications
1
8
0
2
Order By: Relevance
“…Despite the lack of statistically different values, similar patterns of changes in sex steroid (e.g. the increase in T before the final oocyte maturation) have been found in other studies (Crim, Glebe & Scott 1986; Norberg, Bjornsson & Brown 1989; Frantzen, Johnsen & Mayer 1997; Mylonas et al . 1997; Prat, Zanuy & Carrillo 2001; Estay, Diaz, Pedrazza & Colihueque 2003; King & Pankhurst 2003).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Despite the lack of statistically different values, similar patterns of changes in sex steroid (e.g. the increase in T before the final oocyte maturation) have been found in other studies (Crim, Glebe & Scott 1986; Norberg, Bjornsson & Brown 1989; Frantzen, Johnsen & Mayer 1997; Mylonas et al . 1997; Prat, Zanuy & Carrillo 2001; Estay, Diaz, Pedrazza & Colihueque 2003; King & Pankhurst 2003).…”
Section: Discussionsupporting
confidence: 85%
“…(1986) found that OHP is also elevated at this time. Estay et al . (2003) demonstrated the increasing pattern in the OHP level before ovulation and spawning in brown trout.…”
Section: Discussionmentioning
confidence: 99%
“…Like other vertebrates, the gonad maturation of fish is regulated by several sex hormones (Lee and Yang 2002;Estay et al 2003;Ismail et al 2011). In males, androgen and progestin such as testosterone (T), 11-ketotestosterone (11-KT) and 17,20b-dihydoxy-4-pregnen-3-one (17,20b-P), respectively, are known to regulate testicular development by their direct influence on germ cell and also by exerting feedback effects in brain-pituitary-gonad (BPG) axis (Weltzien et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Atlantic salmon females typically ovulate and spawn at GSI > 20. In studies covering different aspects of salmonid reproduction, GSI is typically reported in combination with one or more other methods of maturation index, such as sex hormone analysis (Nagahama and Adachi 1985;Prat et al 1996;Taranger et al 1998;King and Pankhurst 2003), histology of gonad tissues (Sumpter et al 1984;Taranger et al 1999;Estay et al 2003;Grier et al 2007), endoscopy (Ortenburger et al 1996;Swenson et al 2007) and expression of genes related to sexual maturation in relevant tissues (Campbell et al 2006;Luckenbach et al 2008).…”
Section: Introductionmentioning
confidence: 99%